HUBUNGAN STRES AKADEMIK DENGAN INTERAKSI SOSIAL TEMAN SEBAYA PADA MAHASISWA TINGKAT PERTAMA - Dwi Amalia Ramadhan; Darwin Karim; Wan Nishfa Dewi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2022)
Academic stress is a condition in which a student is unable to cope with the pressures and demands received while in a school. It elicits a different response to each individual. One such response is to the social interactions that are formed in each of these individuals. This study aims to investigate the relationship between academic stress and peer social interaction of first-year students. This study used a descriptive correlative research design with a cross sectional approach. Sample of this study was 133 respondents which selected using total sampling techniques. Data was collected using DASS (Depression Anxiety Stress Scales) questionnaires and social interaction questionnaires. The analysis used were univariate and bivariate analysis using Chi Square test. The results of this study showed that the majority of students experienced moderate stress as much as 55 (41.4%), and most had good social interactions with 74 (55.6%). In addition, results of Chi Square test showed that there is a significant correlation between academic stress and peer social interaction in first-grade students with p value (0.005) < alpha (0.05). The study results depict that students mostly able to overcome problems their experienced as well as pressures received. Therefore, it does not impact on their social interactions among other students.Keywords: Academic Stress, Social Interaction, Students